Business process management and supply chain collaboration: a critical comparison - Jiraporn Pradabwong; Christos Braziotis; Kulwant S. Pawar; James Tannock (Logistics Research, 2015)
The link between a firm and supply chain (SC) members has been recognised as one of the key issues for ensuring business success and achieving competitive advantage. Indeed, working across organisational boundaries is required to accomplish effective responses to customers' needs. Our preliminary research confirmed that there are positive relationships between business process management (BPM), supply chain collaboration (SCC), collaborative advantage and organisational performance. This study is a step further and uses a multiple case design to illuminate the results and gain a greater understanding from extensive discussions about these relationships. By means of semi-structured interviews, the three main issues were identified as: (1) the link between BPM and organisational performance; (2) the link between BPM and SCC; and (3) the contextual factors and benefits achieved from working collaboratively with SC partners. The different scenarios of the link between BPM and SCC were developed in a taxonomy, and the case studies were used to illustrate the experience of intra- and inter-organisational practices in the developing economy of Thailand. The case studies' results explain in depth that both BPM and SCC are important for improving organisational performance and competitiveness. BPM not only improves organisational performance directly, but also assists with collaborative activities that in turn help to improve internal capabilities. Additionally, the comparisons in issues relating to firm size, industry type, relationship closeness and relationship length were also included in this study.
Keywords: 650; Business process management; Supply chain collaboration; Collaborative advantage; Case study